2006
DOI: 10.1002/ppul.20456
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of human metapneumovirus infections in hospitalized infants in Spain

Abstract: Human metapneumovirus (hMPV), a condition recently described in the Netherlands, causes lower respiratory infections, particularly in young children and among the elderly. The objective of this study was to describe the characteristics of hMPV infections in hospitalized infants <2 years of age and to compare them to those of infections caused by respiratory syncytial virus (RSV). A prospective study was conducted on the clinical characteristics of infants admitted to hospital for respiratory infection through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
67
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 40 publications
18
67
0
9
Order By: Relevance
“…8 %). A similar seasonality has been observed in studies performed in temperate regions [10,17,19,20]. An interesting finding of this study was an unusually high frequency (51 .…”
Section: Discussionsupporting
confidence: 90%
“…8 %). A similar seasonality has been observed in studies performed in temperate regions [10,17,19,20]. An interesting finding of this study was an unusually high frequency (51 .…”
Section: Discussionsupporting
confidence: 90%
“…HBoV has also been associated with acute respiratory illnesses, predominantly among young children [131133], and has been suggested as a potential cause of acute respiratory illnesses and recurrent wheezing episodes across several studies of preterm infants and children [134136]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Garcia-Garcia et al, 1 recently reported on their findings in a Spanish cohort of 101 pediatric patients hospitalized for HMPV-related respiratory tract infections. Although this article is highly confirmative to their previous study 2 and our matched pairs analysis, 3 it contains some interesting observations and conclusions we would like to comment on.…”
Section: Hmpv Infections Are Frequently Accompanied By Co-infectionsmentioning
confidence: 99%